Implementation of named contracts in Islamic financial institutions - Naerul Edwin Kiky Aprianto (Journal of Islamic Economics Lariba, 2017)
Islam is a complete religion which involves all aspects in life. As social beings, humans cannot live alone and always connect to the others to fulfill their needs. The needs are however various and cannot be fulfilled individually without the helps of the others. To meet the demands of life, the relation between one person and the others should be based on certain deal which is called contracts. In fiqh, there are many classes of contract which are categorized based on the characteristics and specifications of the needs. Therefore, this study aims to analyze the classes of contract that are particularly focused on the named contracts or nominate contracts. It is not only the main requirement for the people doing economic activities and business but also has legal consequences for the people involved.